Research on Management of Digital Library Based on Information Platform. (June 2020) - Wang, Qingjie; Chen, Xuegang; Duan, Sheng; Wang, Luda; Fan, Hongbin
Abstract: How to improve efficiency and service level of digital library by means of computer technology is becoming an urgent problem in higher education. In this context, this paper is developed a new set of digital library management information system. This paper is studied structure of digital library, and we use case modeling to analysis Web platform module, database module, further build the overall system architecture, design main database table. In the process of implementation, database connection is configured, and we do a lot of tests for Web system platform module and reader-discuss-community module. Since the system is online, the website has maintained a good number of visits, and is welcomed by many teachers and students.